KAJIAN GOVERNANCE NETWORKS DALAM PROGRAM THE SUNAN GIRI AWARDS DI KABUPATEN GRESIK - YUNI SITI AISAH (Universitas Negeri Surabaya, 2015)
This paper is about governance networks as a new governance model that suit to been being used for overcome public problem. And also innovation to enhance the quality of public policies and services in public sector. The aim of this paper is to explain the relation involved network participant, Local Government of Gresik Regency and The SunanGiri Foundation during accomplishment of The SunanGiri Awards in order to ensure if the networks are going right as well as governance networks perspective. In recent decade, government has been turned to governance. it involving another sector outside of public sector that could joined up on overcome and solve problems and wicked problems of public that can enhance the public value. Governance networks understood as a model of governance that bring on horizontal equal position of interdependent actors based on negotiation around the regulation that regulating them over interaction and ability to self governing during reaching the main goal together. A good relation among participant could bring the success of a governance networks that applied on as a platform of collaborative. Away better if capital resources, type of tie, policy tools, administrative strategies, accountability structure, and performance management system are managed well. In this sense relation among the participant of networks are seen as the important thing to ensure that governance networks keep on track doing right. This research is going wth descriptive qualitative approach. The datas are primery and secondary datas that have been mixed.As for the source of the data collection techniques using the techniques of interview, observation, and documentation. Meanwhile the focus of this research are Koliba’s structural knowledge that are covering capital resources, type of tie, policy tools, administrative strategies, accountability structure, and performance management system. The result showed that relation among the participant of networks represents relation of Governance Networks. Capital resources describe the ability of each actors for entering the network. Type of tie describe the relation formed by negotiation for build a network. Policy tools describe the rules among participants of network during their role on the network. Administrative strategies describe the coordination among participants of network to acces all the administrative tools on the network. Accountability structure describe the accountability of each actors as well as accountability framework on the governance networks. Performance management system describe monitoring performance of each participants of network during the accomplishment of the program Keywords :New Public Governance, governance, networks, governance networks, relation